Potensi Limbah Pertanian dan Agroindustri Sebagai Sumber Pakan Ternak dalam Pengembangan Ternak Sapi di Desa Jambu, Kecamatan Lenteng, Kabupaten Sumenep - Dia Ayuni; Slamet Widodo (Program Studi Agribisnis, 2023)
During the dry season, breeders face a challenge due to a lack of forage feed. Jambu Village has the second-largest agricultural land area in Lenteng District, which equals 95.67% of the total land area. This land area will produce agricultural waste products. Jambu Village has tofu, and the tempeh agro-industry in the production process produces waste. Agricultural and agro-industrial waste can be used as a source of beef cattle feed. This research aims to 1) know the potential and characteristics of cattle and 2) know the potential of agricultural and agro-industrial waste as a source of feed in the development of cattle in Jambu Village. The characteristics of cattle are described descriptively, while potential agricultural and agro-industrial waste is analyzed based on production and carrying capacity using the conversion formula. As a result of the cattle reared by Madura cattle and intensive rearing patterns, Jambu Village has a livestock population of 402 heads. Agricultural and agro-industrial waste in Jambu Village is capable of producing dry matter of 480,831.65 kg/year and can accommodate and provide animal feed based on dry matter of 210.78 animal unit (AU). Further research regarding the carrying capacity of forage feed needs to be carried out to determine its carrying capacity as animal feed in Jambu Village.